2018
DOI: 10.1186/s12958-018-0338-x
|View full text |Cite
|
Sign up to set email alerts
|

Is Afamin a novel biomarker for gestational diabetes mellitus? A pilot study

Abstract: BackgroundIn search of potential early biomarkers for timely prediction of gestational diabetes mellitus (GDM), we focused on afamin, a vitamin E–binding protein in human plasma.. Afamin plays a role in anti-apoptotic cellular processes related to oxidative stress and is associated with insulin resistance and other features of metabolic syndrome. During uncomplicated pregnancy its serum concentrations increase linearly. The aim of this study was to investigate the suitability of afamin as early marker for pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 40 publications
3
39
0
Order By: Relevance
“…In accordance with the previous studies of our working group [ 19 , 21 ], we found generally higher afamin concentrations in pregnant as well as in non-pregnant women compared to other study cohorts. This phenomenon remains somehow inexplicable and we hypothesise that ethnic differences might contribute to the higher concentrations in our study population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with the previous studies of our working group [ 19 , 21 ], we found generally higher afamin concentrations in pregnant as well as in non-pregnant women compared to other study cohorts. This phenomenon remains somehow inexplicable and we hypothesise that ethnic differences might contribute to the higher concentrations in our study population.…”
Section: Discussionsupporting
confidence: 93%
“…A recently published population-based study including more than 20,000 individuals demonstrated elevated afamin concentrations in individuals with type 2 diabetes mellitus (T2DM) and IR [ 18 ]. Serum afamin concentrations are elevated in patients with polycystic ovarian syndrome (PCOS) and IR [ 19 , 20 ] and in the first trimester of women developing subsequent gestational diabetes mellitus [ 21 , 22 ]. These observations agree with the results of several studies that have suggested cross-links between oxidative stress, the insulin pathway, chronic inflammation and endothelial dysfunction in the pathogenesis of PE [ 23 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been demonstrated that the AFM level was significantly lower in women with uncomplicated pregnancy compared to those with pre-eclampsia (1.2 folds change, p = 0.007) 68 . A correlation between AFM with GDM progression has also been reported 71 whereupon an increased AFM expression was encouraged as an essential reference with high potency for pregnancy-related disorders 68,71 .…”
Section: Proteomic Map Of Umbilical Blood Samples Apod-and Apom-medimentioning
confidence: 91%
“…In a previous study, we were able to demonstrate a strong association between IR and serum afamin concentrations in PCOS patients (19). Additionally, we demonstrated elevated afamin serum concentrations determined during the first and second trimester of pregnancy in patients with GDM (20).…”
Section: Introductionmentioning
confidence: 75%